Total Hip Arthroplasty Using the Conjoined Tendon‐Preserving Posterior Approach: The Modified Posterior Approach with a Minimum of 2‐Year Follow‐Up - Yuto Ozawa; Yusuke Osawa; Taisuke Seki; Yasuhiko Takegami; Hiroki Iida; Hiroto Funahashi; Shiro Imagama (Orthopaedic Surgery)
Purpose The conjoined tendon‐preserving posterior (CPP) approach is a modified posterior approach for total hip arthroplasty (THA) that preserves the short external rotator muscles and most ischiofemoral ligaments. The objective of the present study was to compare the short‐term clinical outcomes, complications, and imaging evaluations of CPP and posterior approaches in THA. Methods This retrospective study included 83 patients from May 2018 to September 2021: 36 patients with 42 hips who underwent THA with the CPP approach (CPP group) and 47 patients with 60 hips who underwent THA with the standard posterior approach (PA group) with a minimum of 2 years of follow‐up. Assessment tools included operative times, blood loss, preoperative and last follow‐up Harris Hip Scores (HHS), postoperative complications, and implant placement angles between the groups. Statistical analysis was performed using chi‐square tests and T‐tests. Results The CPP approach had a significantly longer operative time and greater blood loss compared to the PA group. Preoperative and postoperative HHS were not significantly different between groups. Considering complications, the PA group had one case each of dislocation and infection, and the CPP group had two cases of sciatic nerve palsy, but the difference was not significant. Cup anteversion, inclination and stem anteversion were not significantly different between groups. Conclusion Functional outcomes, complication rates, and implant placement angles were comparable with the posterior approach, and the CPP approach has the potential to reduce postoperative dislocations. However, careful attention should be paid to sciatic nerve palsy during early initiation of the CPP approach, and this study did not demonstrate that the CPP approach was clearly superior to the posterior approach.